CREATING MOBILE DIALER APPLICATION (Case Study : BOGOR â WEST JAVA) - Skawanti, Julia Ratnawulan; Ariwibowo, M. Ridwan (Prosiding International conference on Information Technology and Business (ICITB), 2016)
The phone number is one of the supporting factors are important in running a business. Besides being used to ask for information, the phone number can also be used as a means of reservation and confirmation. Phone number search is difficult and still use the manual search of some communities, especially in the city of Bogor trouble finding the phone number of a business entity. The number of business entities will also make public the difficulty in storing data either manually or electronically. Therefore, we need a dialer program that can provide the mobile phone number data is structured in one application. Mobile dialer is a mobile application that stores data business phone number in Bogor making it easier for people to directly make a phone call without exiting the application. Mobile dialer is built using the Java programming language and platform Android Studio. This application will help people in running and supporting a wide range of activities, although in emergenciesKeywords : mobile dialer , java , android studio , the phone number.Â